Factors controlling the formation of coppice dunes (nebkhas) in the Negev Desert. Issue 7 (28th December 2015) - Kidron, Giora J.; Zohar, Motti
Abstract: Due to their role in increasing fertility, coppice dunes (nebkhas) are regarded by many researchers as important contributors to aridland ecosystems. Yet, despite their frequent occurrence, little information exists regarding the rate and factors that control their formation. The goal of the current study is to examine the formation rate and factors that determine the establishment of coppice dunes in the Hallamish dune field in the western Negev Desert. The rate in which sand and fines, hereafter aeolian input (AI) was trapped and its particle size distribution (PSD) were examined by means of the solidification of 2 m × 2 m plots using surface stabilizers, and by the installation of three pairs of artificial shrubs (SH), three pairs of artificial trees (TR), and a pair of control (CT) plots. Measurements were annually conducted during June 2004 and June 2008, with monthly collection during June 2004 and May 2006. The PSD was compared to coppice dunes located on the fine‐grained playa surface. AI was trapped at SH, while it was not trapped at TR and CT. The annual rate of AI accretion under the canopy was highly variable ranging between 1405 and 13 260 g m −2, with a four‐year average of 5676 g m −2, i.e. 3.8 mm a −1 . It depended upon the wind power, with drift potential having a threshold velocity of U t > 10 m s −1 yielding the higher correlations with the monthly AI ( r 2 = 0.59–0.84). No significant relations were obtained between the monthly AI and shrub height. Sand saltation, suspension and creep are seen responsible for mound formation, which based on the current rates of sand accretion are relatively fast with a 60 cm‐high coppice dune forming within ~150–160 years. The current data highlight the problematic design of some previous research using conventional traps and confining the measurements only to certain seasons. Copyright © 2015 John Wiley & Sons, Ltd.